(untitled) - Doulík, Pavel; Škoda, Jiří; Šedivá, Petra (EduPort, 2022)
The paper entitled The Level of Achievement Motivation in Students of Special Pedagogy as the title implies deals with achievement motivation. The theoretical part is focused on several main topics among which we include motivation, motivation theories and achievement motivation. The research consists of quantitative research of achievement motivation in students of special pedagogy (N = 94) using standardized questionnaire of achievement motivation (LMI). The aim of this paper is to determine the overall level of achievement motivation in university students of that specific field. Subsequently our aim is to find out what results these students achieve in individual dimensions of achievement motivation and likewise whether there are differences between the compared groups. Special education students scored low on the dimensions of confidence in success, flexibility, fearlessness, compensatory effort, independence, and self-control. Average scores were achieved in the dimensions of persistence, dominance, flow, internality, difficulty preference, status orientation, and competitiveness. The highest values were recorded in the dimensions of commitment, willingness to learn and single-mindedness. The results show that there are no statistically or substantively significant differences in the level of overall performance motivation between students in Bachelor's and Master's programmes. There are no statistically or substantively significant differences in the level of overall performance motivation between full-time and part-time students.
Keywords: Special pedagogy; motivation; achievement motivation; motivation theories; motives.